(untitled) (Reflection and Critique Law Magazine, 2022)
The experience of individuals in which, although they do not show symptoms of typical mental illness or intellectual disability, behave socially and/or morally in an abnormal way, has attracted researchers and authors since the beginnings of psychiatry. Currently, this theme has become attractive to areas that go beyond psychology, such as the areas of communication and cinematology, being the motivator of controversies in which they motivate society to think about the role of law in the face of actions committed criminally by alleged individuals. psychopaths about the culpability of the individual. Keywords: Psychopathy; Criminal Law; Psychiatric Disorders.